Ex vivo lipid peroxidation profile of the subjects stratum corneum by the HPLC-TBARS-EVSC protocol - Marques, Gabriela de Argollo (2023)
Background: Considering the need to improve safety and efficacy protocols to evaluate the human stratum corneum (CS) and its interaction with topical and cosmetic formulations by minimally or non-invasive methodologies, the objective of our research work was to improve the performance of the HPLC-TBARS-EVSC methodology (high performance liquid chromatography - thiobarbituric acid reactive substances - stratum corneum ex vivo), exploring the results of a group of subjects. Methods: The study included 18 healthy subjects aged between 19-57 years old (9 females and 9 males) with phototypes from II to V. Two sites in the forearm of each volunteer were randomly delimited and the SC was collected by the tape stripping technique. High performance liquid chromatography (HPLC) was used to quantify the MDA-TBA2 adduct from the tape-stripped SC, irradiated and not by an ultraviolet simulator chamber. Conclusions: Observing the findings of our present investigation, and the statistical approach applied, the use of the ratio between the treatment site and control would be an adequate strategy to better discriminate and evaluate the results. Additionally, an optimal selection of the volunteers to respond specifically to the purpose of the ex vivo assay also can be considered advantageous. It seems that in future studies focusing on the impact of lipid peroxidation induced by UV irradiation, the most suitable subjects are females aged less than 35 years old, with phototype II.